The two-component regulatory system CenK–CenR regulates expression of a previously uncharacterized protein required for salinity and oxidative stress tolerance in Sinorhizobium meliloti - Bensig, Eukene O.; Valadez-Cano, Cecilio; Kuang, ZiYu; Freire, Isabela R.; Reyes-Prieto, Adrian; MacLellan, Shawn R. (Frontiers in Microbiology, 2022)
Genes of unknown function constitute a considerable fraction of most bacterial genomes. In a Tn5-based search for stress response genes in the nitrogen-fixing facultative endosymbiont Sinorhizobium (Ensifer) meliloti, we identified a previously uncharacterized gene required for growth on solid media with increased NaCl concentrations. The encoded protein carries a predicted thioredoxin fold and deletion of the gene also results in increased sensitivity to hydrogen peroxide and cumene hydroperoxide. We have designated the gene srlA (stress resistance locus A) based on these phenotypes. A deletion mutant yields phenotypic revertants on high salt medium and genome sequencing revealed that all revertants carry a mutation in genes homologous to either cenK or cenR. srlA promoter activity is abolished in these revertant host backgrounds and in a strain carrying a deletion in cenK. We also observed that the srlA promoter is autoregulated, displaying low activity in a wildtype (wt) host background and high activity in the srl deletion mutant background. The srlA promoter includes a conserved inverted repeat directly upstream of the predicted -35 subsequence. A mutational analysis demonstrated that the site is required for the high promoter activity in the srlA deletion background. Electromobility shift assays using purified wildtype CenR response regulator and a D55E phosphomimetic derivative suggest this protein acts as a likely Class II activator by binding promoter DNA. These results document the first identified CenK-CenR regulon member in S. meliloti and demonstrate this two-component regulatory system and gene srlA influences cellular growth and persistence under certain stress-inducing conditions.